2015
DOI: 10.1111/pce.12615
|View full text |Cite
|
Sign up to set email alerts
|

Differences in defence responses ofPinus contortaandPinus banksianato the mountain pine beetle fungal associateGrosmannia clavigeraare affected by water deficit

Abstract: We tested the hypotheses that responses to the mountain pine beetle fungal associate Grosmannia clavigera will differ between the evolutionarily co-evolved host lodgepole pine (Pinus contorta var. latifolia) and the naïve host jack pine (Pinus banksiana) and that these responses will be influenced by water availability. G. clavigera inoculation resulted in more rapid stem lesion development in lodgepole than in jack pine; water deficit delayed lesion development in both species. Decreased hydraulic conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 88 publications
6
39
0
Order By: Relevance
“…In general term, much lower phytohormone levels were observed in the wood compared to the bark. Moreover, as in line with our hypothesis (iii), the changes in the phytohormone profile in both bark and wood confirm that S. sapinea disease causes similar stress as water deficit to the pine host (Arango‐Velez et al, ). This is particularly indicated by the elevated levels of ABA and JA in the wood, whereas ABA levels in the bark of host pines showed a decreased level upon S. sapinea infection.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In general term, much lower phytohormone levels were observed in the wood compared to the bark. Moreover, as in line with our hypothesis (iii), the changes in the phytohormone profile in both bark and wood confirm that S. sapinea disease causes similar stress as water deficit to the pine host (Arango‐Velez et al, ). This is particularly indicated by the elevated levels of ABA and JA in the wood, whereas ABA levels in the bark of host pines showed a decreased level upon S. sapinea infection.…”
Section: Discussionsupporting
confidence: 90%
“…tomato DC3000 ( Pto ) interactions by Naseem and Dandekar (). The elevated levels of JA in the wood of the pine host upon S. sapinea disease are consistent with earlier studies on the infection of conifers with the necrotrophic fungus, for example, G. clavigera (Arango‐Velez et al, ; Hudgins, Christiansen, & Franceschi, ; Martin, Tholl, Gershenzon, & Bohlmann, ). Despite a well‐documented crosstalk between SA and JA in plant–pathogen interactions, our results (in the bark: enhanced SA but unaffected JA levels; in the wood: enhanced JA but SA levels below the limit of detection) nevertheless provide new information on the complexity of antagonistic and/or synergistic interactions of SA–JA signalling pathways upon pathogen infection (Kazan & Manners, ; Koornneef & Pieterse, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, lesion size might be affected by differences in soil water content at the two sites; the lodgepole pine site had higher soil water content than the jack pine site at the time of tree harvest likely due to water release through seasonal thawing. Arango-Velez et al (2015), however, also found longer lesions in lodgepole pine than jack pine in an arboretum-based study in Alberta, where both pine species occur at the same field site. Although it is commonly assumed short lesions indicate host plant resistance (Raffa and Berryman, 1983;Krokene and Solheim, 1998), assessment of qualitative and quantitative changes in phloem chemistry following fungal inoculation might be more relevant to explain tree resistance against bark beetles (Peterman, 1977;Berryman, 1982, 1983;Paine et al, 1997).…”
Section: Effect Of Water and Biological Treatment On Tissue Defense Rmentioning
confidence: 76%
“…These results also add to our understanding of how plant architecture and the attacking agent interact to influence the expression of induced responses. Chemical induction in conifers can extend beyond anatomical responses, as previous studies have detected changes well beyond lesions, sometimes in needles of trees induced on the stem (Arango-Velez et al, 2016;Bonello & Blodgett, 2003;Krokene, Solheim, & Krekling, 2003;Sherwood & Bonello, 2016;Villari et al, 2012). The extent to which the distances involved reflect local chain reactions due to cell injury, hormonal elicitors, or diffusion is unknown.…”
Section: Discussionmentioning
confidence: 99%